Certain Types of Soft Sets in the Games Theory - Esmaeel , R. B. (Iraqi Journal of Science, 2025)
Some topological games with soft set theory became important in real life techniques, especially, in economics. Throughout the present work, we introduce new types of soft sets, say, - - -open sets and some of their investigations are studied. In addition, some new kinds of soft separation axioms will be defined, and their implications are studied. Finally, numerous sorts of soft topological games that depend on soft separation axioms are investigated. We prove the important conditions that the first and second players win the proposed games.